SIGNIFIKANSI PENGUASAAN MUFRADAT TERHADAP KEMAMPUAN BERBICARA BAHASA ARAB DI PONDOK PESANTREN AL-KAUTSAR TANJUNGPINANG - zaimah, zaimah (Armala, 2024)
Arabic is one of the international languages that students must master to face the increasingly advanced era of globalization. This research aims to provide an overview of the mastery of vocabulary (mufradat) and Arabic speaking patterns by the students. Whether the two have a significant relationship or influence or not. The results of the research show that the students of Al-Kautsar Islamic boarding school have good mastery of mufradat with a percentage of 74.95 and the ability to speak Arabic also shows good results with a percentage of 68.08%. Then, it is known that rxy: 0.939 > r-table at the 5% and 1% significance levels (0.939>0.203>0.264). Thus, between the mastery of mufradat and the ability to speak Arabic of the students of the al-Kautsar Islamic Boarding School, Tanjungpinang, there is a very strong significant influence.